Research trends about Visual Basic as a programming language in the learning process: a bibliometric analysis - Nurjaman, Adi; Juandi, Dadang; Supriyadi, Edi; Hidayat, Wahyu; Darhim, Darhim (Institute of Advanced Engineering and Science, 2024)
This study employs bibliometric analysis to systematically explore the Visual Basic (VB) education research landscape, identifying significant trends, influential authors, and future research directions. Utilizing data from Scopus-indexed journals, we examined 529 papers published between 1994 and October 2023, identified through the keywords